Experimental life : vitalism in Romantic science and literature - Mitchell, Robert, 1969- (The Johns Hopkins University Press, 2013)
If the objective of the Romantic movement was nothing less than to redefine the meaning of life itself, what role did experiments play in this movement? While earlier scholarship has established both the importance of science generally and vitalism specifically, with regard to Romanticism no prior study has investigated what it meant for artists to experiment - and how those experiments related to their interest in the concept of life. This study draws on approaches and ideas from contemporary science studies, proposing the concept of experimental vitalism to show both how Romantic authors appropriated the concept of experimentation from the sciences and the impact of their appropriation on post-Romantic concepts of literature and art. The author navigates complex conceptual arenas such as network theory, gift exchange, paranoia, and biomedia and introduces new concepts, such as cryptogamia, chylopoietic discourse, trance-plantation, and the poetics of suspension. As a result, this book is a wide-ranging summation and extension of contemporary literary studies, the history of science, cultural critique, and theory.